GEOHERITAGE PRELIMINARY EVALUATION AND ITS IM-PLICATION ON GEOTOURISM POTENTIAL IN WEST BAN-DUNG, BANDUNG, INDONESIA - Hana Nur Aini; M Chairil Talib; Rachmat Heryadi; Achmad Djumarma Wirakusumah (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2021)
Geoheritage is a term of geological sites that fulfill certain values and criterias which can impact the local community. The unique tectono-volcanic History of Bandung has produced several impressive geodiversity. This research aims to evaluate six geological sites (Bugbrug Waterfall Lava Ramp, Cimahi Waterfall Columnar Joint, Panganten Waterfall Columnar Joint, gunung Batu Fault Scarp, Cihanjuang Ignimbrite, and Tangkuban Parahu Ratu Crater) which are potential as Geoheritage in West Bandung District, Bandung, West Java. Quantitative evaluation was done through several parameters which include values that are important for geoheritage such as: Intrinsic and Scientific Value, Education Value, Economic Value, Conservation Value, and Added Value. This evaluation method will produce scores that will further be analyzed through qualitative means by using SWOT (Strength, Weak-ness, Opportunity, and Weakness) method and its implication on geotourism potential. Quantitative analysis shows that Geodiver-sity of West Bandung shows a good potential as Geoheritage with the final score ranges between 50.83 – 74.17%. The SWOT analysis was applied through strengths of geoheritage potential in this area, especially from Scientific, Economic, and Aesthetic Parameters. The uniqueness of West Bandung Geoheritage Potetial is currently slightly diminished due to the lack of public educa-tion aspects, the lack of significant cultural and ecologic value in several sites.